Use of Radical Oxygen Species Scavenger Nitrones to Treat Oxidative Stress-Mediated Hearing Loss: State of the Art and Challenges - Varela-Nieto, Isabel; Murillo-Cuesta, Silvia; Rodríguez-de la Rosa, Lourdes; Oset-Gasque, María Jesús; Marco-Contelles, José (Frontiers in Cellular Neuroscience, 2021)
Nitrones are potent antioxidant molecules able to reduce oxidative stress by trapping oxygen and nitrogen reactive species. The antioxidant potential of nitrones has been extensively tested in multiple models of human diseases. Sensorineural hearing loss has a heterogeneous aetiology, genetic alterations, ageing, toxins or exposure to noise can cause damage to the hearing receptor. Despite the many differences in the noxious stimuli there are several common mechanisms, being one of them the generation of free radicals and redox imbalance. Therefore, targeting oxidative stress-mediated hearing loss has been the subject of much attention. Here we review the chemistry of nitrones, the existing literature on their use as antioxidants and the general state of the art of antioxidant treatments for hearing loss.